2016
DOI: 10.22452/mjlis.vol21no2.5
|View full text |Cite
|
Sign up to set email alerts
|

Publication and citation patterns of Korean LIS research by subject areas

Abstract: Many researchers have suggested careful application of bibliometric indicators to research evaluation because of many factors including disciplinary norms that influence the publication and citation behaviors of researchers. Although some researchers have examined different bibliometric patterns across disciplines, relatively few scholars have focused on whether research performance should be evaluated in a uniform manner across research domains within a single discipline, especially in a multidisciplinary fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Zhao et al (2021) have conducted a comparative analysis of the research GKMC 73,1/2 productivity of LIS schools of China and the USA and found the growth in WoS publications by Chinese LIS schools. Yang et al (2016) have analyzed the publication and citation patterns of Library and Information research of Korea for identifying the most popular and influential subject areas. Bangani and Onyancha (2021) have evaluated the scientific productivity of national research foundation-rated researchers exploring the impact of their research during 12 years.…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et al (2021) have conducted a comparative analysis of the research GKMC 73,1/2 productivity of LIS schools of China and the USA and found the growth in WoS publications by Chinese LIS schools. Yang et al (2016) have analyzed the publication and citation patterns of Library and Information research of Korea for identifying the most popular and influential subject areas. Bangani and Onyancha (2021) have evaluated the scientific productivity of national research foundation-rated researchers exploring the impact of their research during 12 years.…”
Section: Related Workmentioning
confidence: 99%